O processo de formação do cirurgião-dentista e a prática generalista da odontologia: uma análise a partir da vivência profissional - Cordioli, Otavio Fernando Genta [UNIFESP] (2006)
This dissertation comprises an investigative approach to the formation process in Dentistry, from the perspective of students that had graduated until five years ago and engaged in lato sensu post graduation courses, while experiencing a generalist practice of the profession. This research aims at knowing the conceptions of generalist practice, mapping the difficult and easy situations faced during the course and offering suggestions for changing the graduation courses, based on this practice perspective. An exploratory research was chosen for this work, considering quantitative and qualitative approaches. The data were collected through questionnaires related to the theme researched, and the analysis of concordance and discordance degrees were observed, quantified and shown in graphs. Semi structured interviews were also used and the results were investigated through a Thematic Analysis. The main findings show the essential aspects that are still the limitations for the development of the expected graduated profile, published by the Brazilian Curricular Policies, especially those related to a generalist practice of the profession. Among the elements observed in this investigation process, the most relevant were the lack of interaction between theory and practice, a vision of Dentistry out of the real context and a consequent lack of preparation for the market. Furthermore, the research also indicated the existence of an intra-professional emphasis with no integration with other areas of Health Care, an inadequate formation for the practice in the public systems (SUS), an inadequate preparation for managing the practice and self development and no preparation for social interaction with other professionals and patients. This landscape pointed to the necessity of changing these aspects, incorporating the improvement of learning scenarios with a focus on an integrated clinical teaching proposal and on a flexible curriculum with more contents and disciplines integration. Other actions should also be considered such as the implementation of interdisciplinary practices, a better preparation of undergraduate students in order to lead them to independent studies and research through motivating the scientific initiation, and finally more investments in the development of professors. This investigation suggests the establishment of new interlocutions and the enhancement of new research opportunities, considering Dentistry teaching and learning as an area that provides knowledge and practices production.